2011
DOI: 10.1118/1.3560881
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quantitative accuracy of a commercially available positron emission mammography scanner

Abstract: Applying corrections for count rate effects, attenuation, and scatter will be essential for the PEM Flex Solo II to be able to produce quantitatively accurate images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…Between-plane resolution degrades as detector separation increases, so this PEM design is well-suited to hand imaging where the detector separation is only 4.5 – 6 cm. Springer et al determined that applying corrections for count rate, attenuation and scatter was essential for the PEM Flex Solo II system, with the least attenuation effects seen in phantoms of thickness 4 cm [43]. A dedicated small-parts system like PEM has high spatial resolution, and in breast applications, has been shown to have comparable sensitivity and specificity to MRI for breast lesions [44].…”
Section: Discussionmentioning
confidence: 99%
“…Between-plane resolution degrades as detector separation increases, so this PEM design is well-suited to hand imaging where the detector separation is only 4.5 – 6 cm. Springer et al determined that applying corrections for count rate, attenuation and scatter was essential for the PEM Flex Solo II system, with the least attenuation effects seen in phantoms of thickness 4 cm [43]. A dedicated small-parts system like PEM has high spatial resolution, and in breast applications, has been shown to have comparable sensitivity and specificity to MRI for breast lesions [44].…”
Section: Discussionmentioning
confidence: 99%
“…Broadening the application of the PEM beyond the breast to use PUV as a quantitative metric must address several new considerations, namely the PEM uptake value's lack of standardization or correction. A phantom study found that quantitative accuracy of the PEM (based on administered dose) was affected by thickness of the phantom[10] if this finding were reproducible in vivo, then we would see variations in the correlation between SUV and PUV in smaller objects of interest such as the hands versus larger objects such as the thigh. Although our sample size was too small to appreciate such differences in a statistically significant way, this finding would be interesting to evaluate in a larger study.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the anisotropic resolution on our results, and potential benefits of isotropic resolution for lesion detection, are not clear. Another consequence of tomosynthesis is that image quantification of tracer uptake is typically compromised (26), although there are approaches to overcome this limitation (27). PET detectors that completely surround the breast provide much higher photon detection sensitivity than scanning-detector systems, and as a result, lower image noise would be expected from such systems for a given acquisition protocol.…”
Section: Discussionmentioning
confidence: 99%